2-Mm Diameter Operative Tendoscopy of the Tibialis Posterior, Peroneal, and Achilles Tendons: A Cadaveric Study. (April 2020) - Stornebrink, Tobias; Stufkens, Sjoerd A. S.; Appelt, Daniel; Wijdicks, Coen A.; Kerkhoffs, Gino M. M. J.
Background: Technical innovation now offers the possibility of 2-mm-diameter operative tendoscopy with disposable arthroscopes and tablet-like control units. The promises of new technology should be critically scrutinized. Therefore, this study assessed whether 2-mm-diameter operative tendoscopy of the tibialis posterior, peroneal, and Achilles tendons was safe and effective in a cadaveric model. Methods: A 2-mm-diameter arthroscopic system was used to perform a tendoscopic procedure in 10 nonpaired, fresh-frozen, human ankles. Standard tendoscopic portals were utilized. Visual examination and operative reach with tailored tendoscopic instruments within the tendon sheaths were recorded and documented. Adhesiolysis and vincula resections were performed. After dissection, distances between portal tracts and neurovascular structures were measured and the tendons were inspected for signs of iatrogenic damage. Results: The entire tendon sheath and tendon of the tibialis posterior, peroneus brevis, and Achilles tendons were visualized and reached with tailored operative instruments. The proximal part of the peroneus longus tendon was visible and reachable from proximally up to the cuboid bone distally. Adhesiolysis and vincula resections were successfully performed in all specimens. The mean distances between portal tracts and local neurovascular structures ranged between 9.4 and 19.2 mm and there were no cases of contact. None of the tendons showed signs of iatrogenic damage. Conclusion: Two-millimeter-diameter operative tendoscopy provided safe and effective visualization and operative reach of the tibialis posterior, peroneal, and Achilles tendons. Clinical Relevance: Compared with current practice, 2-mm-diameter operative tendoscopy has the potential to make tendoscopy around the ankle less invasive and more accessible. Diagnostic, interventional, and second-look procedures might be performed at substantially reduced risk, time, and costs.